2011
DOI: 10.1186/1749-799x-6-47
|View full text |Cite
|
Sign up to set email alerts
|

A genetic association study between growth differentiation factor 5 (GDF 5) polymorphism and knee osteoarthritis in Thai population

Abstract: ObjectiveOsteoarthritis (OA) is a multi-factorial disease and genetic factor is one of the important etiologic risk factors. Various genetic polymorphisms have been elucidated that they might be associated with OA. Recently, several studies have shown an association between Growth Differentiation Factor 5(GDF5) polymorphism and knee OA. However, the role of genetic predisposing factor in each ethnic group cannot be replicated to all, with conflicting data in the literatures. Therefore, the aim of this study wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
28
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 28 publications
0
28
0
1
Order By: Relevance
“…A meta-analysis of data from Europe and Asia (more than 11 000 individuals) confirmed the association between rs143383 SNP and knee OA [100]. In recent studies, the TT genotype of the rs143383 SNP was found to be associated with an increased risk of knee OA in a Thai population [101] and the T allele of the same SNP was associated with a 17% increased risk of knee OA in Caucasians [102]. …”
Section: Genetic Determinants Of Osteoarthritismentioning
confidence: 92%
“…A meta-analysis of data from Europe and Asia (more than 11 000 individuals) confirmed the association between rs143383 SNP and knee OA [100]. In recent studies, the TT genotype of the rs143383 SNP was found to be associated with an increased risk of knee OA in a Thai population [101] and the T allele of the same SNP was associated with a 17% increased risk of knee OA in Caucasians [102]. …”
Section: Genetic Determinants Of Osteoarthritismentioning
confidence: 92%
“…Moreover, OA cases were defined with different criteria in different studies, which might be one of sources of observed heterogeneity. Some studies defined their patients using the K/L classification and/or ACR criteria [29][30][31][32][33][34][35]37,[39][40][41][42][43], while other studies defined their patients using the TKR [28,36,38]. This discrepancy on those key characteristics of the participants,such as age and BMI, might also lead to the heterogeneity [34].…”
Section: Discussionmentioning
confidence: 99%
“…The remaining studies (n=38) were reviewed and additional 22 studies were excluded for not being case-control or cohort studies (n=6), not relevant to the GDF5 gene (n=3), not related to OA or LDD (n=7), or unavailable genotyping data (n=6). In the final analysis, there were 15 articles that were combined to perform an association analysis of rs143383 with OA and/ or LDD [28][29][30][31][32][33][35][36][37][38][39][40][41][42][43].The characteristics of these included articles were presented in Table 1. All the studies conformed to HWE in the control group.…”
Section: Characteristics Of Studiesmentioning
confidence: 99%
See 2 more Smart Citations